2018
DOI: 10.1002/gps.4970
|View full text |Cite
|
Sign up to set email alerts
|

Does the Geriatric Depression Scale measure depression in Parkinson's disease?

Abstract: Background The Geriatric Depression Scale (GDS) is recommended for screening depression in individuals with Parkinson's disease (PD). Empirical evidence, however, is limited regarding its validity and factor structure in PD. Thus, the current study sought to evaluate the convergent and divergent validity of the GDS, as well as the structure and validity of the derived factors. Method Nondemented individuals with PD (n = 158) completed the GDS‐30, and items were subjected to a principle component analysis. Geri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 41 publications
1
17
0
2
Order By: Relevance
“…The results showed that this scale could be a reliable screening tool for geriatric depression in Vietnam. Our findings are consistent with previous studies that have demonstrated that this scale can be used effectively to screen for depression in the elderly in many countries worldwide with different versions of the number of items [31,32].…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that this scale could be a reliable screening tool for geriatric depression in Vietnam. Our findings are consistent with previous studies that have demonstrated that this scale can be used effectively to screen for depression in the elderly in many countries worldwide with different versions of the number of items [31,32].…”
Section: Discussionsupporting
confidence: 93%
“…A recent study by Lopez and colleagues 37 investigated whether the 30-item GDS in fact measures depression in non-demented individuals with PD. Convergent validity was moderate between the GDS total score and other individual depression items (MDS-UPDRS depression item, Hamilton Depression Rating Scale depression item) and there was poor divergence with other mood measures (Apathy Scale, State-Trait Anxiety Inventory, modified Fatigue Impact Scale).…”
Section: Discussionmentioning
confidence: 99%
“…The most significant was the difference in depression-specific scales; the GDSS was used in PPMI while the HDRS was used in PDBP. Prior studies have raised concerns about there only being a moderate correlation between the GDSS and HDRS [29], however other analyses of the two scales have found they both exhibit good sensitivity and specificity for the diagnosis of depression in PD [24]. The presence of pRBD was also assessed with different methods, however both have been found to have good sensitivity and specificity for screening purposes [30].…”
Section: Discussionmentioning
confidence: 99%